ANALISIS MISKONSEPSI PADA MATERI PECAHAN BENTUK ALJABAR DITINJAU DARI GAYA KOGNITIF SISWA KELAS VII SMP NEGERI 14 PALU - Ainun Mardiah M. Liname; Mustamin Idris; I Nyoman Murdiana (Jurnal Elektronik Pendidikan Matematika Tadulako, 2021)
The purpose of this study is to describe students misconceptions on the material of algebraic fractions in terms of the cognitive style of seventh grade students of SMP Negeri 14 Palu. This type of research is descriptive qualitative research. The subjects of this study were 2 students consisting of one student who had a reflective cognitive style and one student who had an impulsive cognitive style, taken from 17 students of class VII Swallow at SMP Negeri 14 Palu. Misconceptions were identified using a written essay test accompanied by the Certainty of Response Index (CRI) method and interviews. The results of this study indicate that students who have reflective and impulsive cognitive styles experience misconceptions: (1) students misconceptions with reflective cognitive style occur in connecting between concepts of fractional division operations in algebraic forms, the cause of students misconceptions with reflective cognitive style comes from students wrong thinking and lack of student learning experience, (2) students misconceptions with impulsive cognitive style occur in using the concepts of addition and subtraction and the concept of adding integers, misconceptions in connecting between concepts and misconceptions in interpreting the concept of adding terms like algebraic forms, the cause of students misconceptions with impulsive cognitive style comes from students' wrong thinking, lack of accuracy of students in solving problems, lack of student learning experience and have a wrong understanding of the concept.